ARIAS learning model based on a contextual approach to increase the mathematical connection capacity - Swastika, Galuh Tyasing; Narendra, Risang (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2019)
The purpose of this study is to improve the mathematical connection capacity of students in Calculus I by applying the ARIAS learning model based on a contextual approach. The instrument used to determine the increase in students' mathematical connections in this study is the activity observation sheet and the test of learning outcomes. While during the learning process, the discussion with the function material is used. This research has two cycles in which each consists of planning, action, observation and reflection. In the previous learning, the preliminary tests were given to the students, as a previous reflection. The results of pre-reflection learning showed that 63% had not yet completed a score of ≥75. The results of the study show that ARIAS learning models based on contextual approaches can gradually increase students' mathematical connection skills. This is based on the results of increased student activity and the results of an increase in learning tests in cycles I and II. The percentage of student activity is 80.70% (good category). The student's activity is 86.40% (good category) in cycle II. The student's connection capacity in the first cycle is 10.16 (good category) and a score of 12.79 (excellent category) in the second cycle.